Trade Tariff, Wage Gap and Public Spending - Michele G. Giuranno; Antonella Nocco (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies the interplay between the wage gap and government spending in a small open economy facing a shock in trade policy. We consider a specific factor model with an export sector, which uses skilled labour, and an import-competing sector, which uses unskilled labour. We find the conditions under which there exists an inverse (direct) relation between trade lib-eralization (protection), which increases (decreases) the skilled-unskilled wage gap, and the level of government expenditure. We also show how either an unbalanced distribution of political bargaining power, or tariff revenue co-financing public spending may break this direct relation.
Keywords: F15; F16; H50; 330; wage gap; trade liberalization; positive political economy